Cues an analysis of student perceptions of college environments of selected institutions of higher learning - Ambatali, Josephini P. Sister 1933-
The perceptions of 2,115 students from 39 colleges/universities throughout the country including 18 PAASCU-accredited schools and their neighboring schools which offer similar programs were gathered using the College and University Environment Scales of Dr. C. Robert Pace to measure college environment. Pearson's ANOVA, factor analysis, item/scale correlation, and K-R 20 reliability were applied to test the hypotheses and the psychometric characteristics such as an institution's affiliation with certain school associations, the predominant sex of its student population, its geographical location, and the proportion of its Liberal Arts, Education and Commerce enrolments. However, an institution's professed religious orientation, its faculty/student ratio, and the existence of a Graduate Department did not affect student perceptions. Institutions perceived as "practical" were also considered "aware"; those with high degree of "community" were also considered "practical"; "prestigious" institutions were also found to be "practical", "aware", and "able to place graduates".